FEA simulation of heat transfer through an emulated piece of meat with rectangular geometry in a dip shrink tank - Velázquez Ortega, José Luis; López Pérez, Jorge; Cruz Romero, Pablo (Acta Universitaria, 2022)
Producing safe food is a priority. Hazard analysis and critical control points (HACCP) is used in food industry for the control of biological hazards. However, making portions allows recontamination, putting this attribute at risk, a problem that has been controlled by adding some other process, such as the use of high pressure processing: an efficient, but costly and time-consuming method. The purpose of this research is to modify the heat-shrinking process of portioned product packaging and convert it into a critical control point to guarantee its safety, since, until now, it is conceived solely to protect the food from external agents, covering it in a shrinkable plastic container and immersing it in a tank with hot water. To do this, temperature, flux, and time variables were obtained through computational simulations in an emulated piece of meat, using finite element analysis to estimate and evaluate the heating process.